2023
DOI: 10.1001/jamapediatrics.2022.4912
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Saline vs Gluconate/Acetate–Buffered Solution vs Lactate-Buffered Solution on Serum Chloride Among Children in the Pediatric Intensive Care Unit

Abstract: ImportanceMost children admitted to pediatric intensive care units (PICUs) receive intravenous fluids. A recent systematic review suggested mortality benefit in critically ill adults treated with balanced solutions compared with sodium chloride, 0.9% (saline). There is a lack of clinically directive data on optimal fluid choice in critically ill children.ObjectiveTo determine if balanced solutions decrease the rise of plasma chloride compared with saline, 0.9%, in critically ill children.Design, Setting, and P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 39 publications
0
4
0
Order By: Relevance
“…This finding is consistent with a systematic review and subsequent randomized trial in adult kidney transplant recipients, and a randomized trial in children on intensive care. 23 , 24 , 25 A recent randomized trial in deceased donor kidney transplant recipients found that Plasma-Lyte-148 reduced the incidence of delayed graft function compared with 0.9% sodium chloride; our study did not assess this outcome in children. 26 We observed no difference in transplant kidney function, graft survival, or patient survival between the Plasma-Lyte-148 and standard fluid groups, although the study was not powered for these outcomes.…”
Section: Discussionmentioning
confidence: 88%
“…This finding is consistent with a systematic review and subsequent randomized trial in adult kidney transplant recipients, and a randomized trial in children on intensive care. 23 , 24 , 25 A recent randomized trial in deceased donor kidney transplant recipients found that Plasma-Lyte-148 reduced the incidence of delayed graft function compared with 0.9% sodium chloride; our study did not assess this outcome in children. 26 We observed no difference in transplant kidney function, graft survival, or patient survival between the Plasma-Lyte-148 and standard fluid groups, although the study was not powered for these outcomes.…”
Section: Discussionmentioning
confidence: 88%
“…Massive infusion of SGI is inevitably accompanied by an infusion of large amount of chlorine, thus increasing the risk of hyperchloremic metabolic acidosis. 7 , 8 For SG-MESAI, sodium acetate solution, which contains potassium chloride, magnesium chloride, and sodium acetate, is used as the carrier instead of sodium chloride. Therefore, SG-MESAI can greatly reduce the risk of hyperchloremia after infusion while maintaining electrolyte-fluid and acid-base balance.…”
Section: Discussionmentioning
confidence: 99%
“…The subjects were excluded if they met any of the following exclusion criteria: (1) severe hypernatremia, hyperchloremia, and hypercalcemia before surgery, defined as serum sodium>152 mmol/L, serum calcium>12 mg/dL (>3.00 mmol/L), or serum chlorine>1.06 mmol/L. Assessment was made by combining laboratory tests with clinical manifestations, including sleepiness, coma, delirium, and insanity; 2) pulmonary edema, cerebral edema, intracranial hemorrhage, and heart failure; (3) liver and kidney function indicators more than twice the upper limit of the normal range; 4) having a history of organic brain diseases or cerebral hemorrhage, having organic heart diseases or wearing a cardiac stent, and having a history of mental illnesses and disturbance of consciousness; (5) abnormal results on coagulation function test and electrolyte test (abnormalities assessed by investigators as clinically significant); (6) having received dialysis treatment within one month before surgery; (7) having been judged as lacking the capacity to give informed consent; (8) having participated in other drug clinical trials in the past three months; (9) having a known allergy to the investigational drug and/or its ingredients (eg, gelatin plasma substitute, α-galactose); (10) having a history of hypothyroidism; (11) pregnancy, lactation, or preparing for pregnancy; (12) scheduled for neurosurgery; (13) any other conditions that disqualified the subjects for the present study, as judged by the investigator.…”
Section: Participantsmentioning
confidence: 99%
“…After reviewing the titles and abstracts, 1, 334 articles were excluded, and 59 studies were selected for the second screening after additionally excluding 64 duplicated studies. Finally, 13 full-text articles involving 38,798 patients were included in this meta-analysis [11,[22][23][24][25][26][27][28][29][30][31][32][33]. Of these studies, 10 were randomized controlled trials (RCTs), and 3 were cohort studies.…”
Section: Literature Search and Study Characteristicsmentioning
confidence: 99%